Rapid purification of glial cells using immunomagnetic separation. - Wright, A; Fitzgerald, J; Colello, R (1997)
By purifying glial cells from brain tissue containing a heterogeneous cell population, a number of interactions that define glial cell diversification and function within the central nervous system have been determined. The current methods for purifying glial cells, however, can be time consuming and costly. In the following study we have adapted the technique of immunomagnetic separation to separately enrich 0-2A progenitor cells and astrocytes from the rat central nervous system (CNS). In this procedure, tissue from the CNS was enzymatically dissociated and incubated in a primary antibody specific to a surface antigen found on the target cell type (e.g. A2B5 or RAN-2). The target cells were then immunologically coupled to magnetic beads, which were precoated with a secondary antibody specific to the primary, and then separated out from the heterogeneous cell population using a magnetic field. We found that the immunomagnetic separation procedure, which was completed within 2 h, produced a near pure population of glial cells (> 99%). This was confirmed by the absence of unbound cells in the bead-bound fraction. The identification and viability of bead-bound cells were established by culturing these cells and subsequently examining their morphology and antigenic expression. This study shows that glial cell types can be separated out of brain tissue to near purity using immunomagnetic separation. This simple procedure is reliable, inexpensive, and achieves levels of purity and viability comparable with currently available techniques of immunopanning and fluorescence-activated cell sorting, within a fraction of the time.